Mogroside V and mogrol: unveiling the neuroprotective and metabolic regulatory roles of Siraitia grosvenorii in Parkinson’s disease - Tang, Quan; Qiu, Rui; Guo, Mei; Wang, Lili; Zhang, Yan; Chen, Yuewen; Cheng, Yong (Frontiers in Pharmacology, 2024)
Introduction: Siraitia grosvenorii (Swingle) C. Jeffrey, is an edible and traditional medicine widely used in China. Mogroside V (MGV) and mogrol (MG) are its main active ingredients, which have been found to be effective in the treatment of neurodegenerative diseases recently. However, whether they can effectively treat Parkinson's disease (PD) and their underlying mechanisms have not been sufficiently explored. In this study, we investigated the neuroprotective and metabolic regulatory effects of MGV and MG on PD.Using SH-SY5Y cell models and an MPTP-induced mouse model of PD, we evaluated the compounds' efficacy in mitigating MPP+-induced neurotoxicity and ameliorating motor deficits and dopaminergic neuron loss. Employing widely targeted metabolomics and bioinformatics analysis to investigate the Metabolic imbalance rectification caused by MGV and MG treatment. The vivo experimental protocol encompassed a 14-day drug administration regimen with mice randomly allocated into six groups (n=9) receiving distinct compound dosages including a control group, a model group, MGV-H (30 mg/kg/day), MGV-L (10 mg/kg/day), MG-H (15 mg/kg/day), and MG-L (3 mg/kg/day).Our findings revealed that pre-treatment with MGV and MG significantly enhanced cell viability in SH-SY5Y cells exposed to MPP+, demonstrating a potent protective effect against neurotoxicity. In the MPTP mouse model, MGV-H, MGV-L, and MG-H significantly enhanced motor coordination as assessed by the rotarod test (p < 0.05); MGV-L and MG-H evidently inhibited dopaminergic neuronal loss in the substantia nigra pars compacta (p < 0.05). Furthermore, metabolomic analysis of the substantia nigra highlighted the restoration of metabolic balance, with MGV-L and MG-H impacting 160 differential metabolites and modulating key pathways disrupted in PD, including sphingolipid metabolism, fatty acid metabolism, and amino acid metabolism. Notably, treatment with MGV-L and MG-H led to the regulation of 106 metabolites, showing a recovery trend towards normal levels, which constitutes approximately 17.5% of the identified metabolites. Key metabolites such as n-acetyl-l-glutamate, hexadecanoic acid, and 9-octadecenal were significantly altered (p < 0.05), underscoring their broad-spectrum metabolic regulatory capacity.This study underscores the potential of natural compounds in developing comprehensive treatment strategies for neurodegenerative diseases, paving the way for future clinical research to validate the therapeutic efficacy of mogrosides in PD.